Алгебра алгоритмов, базирующаяся на данных - Акуловский, В.Г. (Кибернетика и системный анализ, 2012)
На основі модифікованої моделі ЕОМ Глушкова побудовано систему алгоритмічних алгебр. Дані формалізовані й специфіковані на вході й виході Д-операторів і, таким чином, побудований формальний апарат базується на даних. Доведено деякі властивості Д-операторів і операцій, що утворюють сигнатуру алгебри, а також можливість побудови похідних Д-операторів. A system of algorithmic algebras is formed based on a modified Glushkov’s computer model. Data are formalized and specified at the input and output of D-operators and thus the formal apparatus is based on data. Some properties of D-operators and of operations that form the signature of algebra are proved and setting up derived D-operators is shown to be possible.